The Effectiveness of the PUPM Scholarship Program in Enhancing Educational Access for Students at Muhammadiyah Islamic Boarding Schools - Janah, Trisania Nurul; Jihaan S , Nuur; Mediyastuti S , Meti; Prabu PM , Seanu; Supriatna, Riyan; Insani, Mohamad Ridho; Rahardian, Ramaditya (Journal of Administration, Governance, and Political Issues, 2025)
This study aims to evaluate the effectiveness of the PUPM Scholarship Program in enhancing educational access for students at Muhammadiyah Islamic Boarding Schools (Pesantren). Employing a qualitative research design, data were collected through in-depth interviews with scholarship recipients, program administrators, and key stakeholders. The findings reveal that the program significantly alleviates financial barriers, allowing students—particularly those from low-income backgrounds—to pursue education without the burden of tuition and related costs. Additionally, the program provides academic support, including tutoring and language enrichment in Arabic and English, which enhances students’ learning experiences and self-confidence. Beyond academics, the scholarship fosters personal development by encouraging leadership and community service, aligning with Muhammadiyah’s core values. However, challenges remain, including limited awareness among potential applicants, initial communication gaps, and concerns over long-term financial sustainability. Participants emphasized the need for improved outreach and donor engagement to ensure the program’s growth and inclusivity. Overall, the PUPM Scholarship Program demonstrates strong potential in transforming the educational landscape of Muhammadiyah Pesantren. By addressing its existing challenges, the program can continue to empower underprivileged students, promote social responsibility, and contribute to a more equitable education system aligned with the vision of Muhammadiyah.